Distance technology of foreign language learning (Eurasian Journal of Philology Science and Education, 2016)
This article deals with the problems of distance foreign language learning. Distance learning of foreign languages connects the teacher with students closely through activity, and a person’s activity can be seen in exploring his behavior. In distance learning the student’s activity is aimed at the rapid transfer of necessary knowledge and skills, as well as at the development of the personality capable of self-control. The diligence of teaching activity in distance learning system is implemented in different ways, mainly through special educational materials, its focus on one direction and its distribution, the most effective forms and methods of teaching, as well as on the effective use of potentials of the teacher and the student and its beneficial use in practice. In accordance with this, the student and the study group have an opportunity to study foreign languages via the computer actively, form the necessary communicative activities and skills, and develop personal features which are necessary for an individual, for his conscious and active work.
Keywords: distance learning; technology; communication; formation; computer; foreign language; activity.